Water, food and livelihoods in river basins - Cook, Simon E.; Fisher, Myles J.; Andersson, Meike S.; Rubiano Mejía, Jorge Eliécer; Giordano, Mark (Informa UK Limited, 2009)
Conflicting demands for food and water, exacerbated by increasing population, increase the risks of food insecurity, poverty and environmental damage in major river systems. Agriculture remains the predominant water user, but the linkage between water, agriculture and livelihoods is more complex than “water scarcity increases poverty”. The response of both agricultural and non-agricultural systems to increased pressure will affect livelihoods. Development will be constrained in closed basins if increased demand for irrigation deprives other users or if existing agricultural use constrains non-agricultural activities and in open basins if agriculture cannot feed an expanding or changing population or if the river system loses capacity due to degradation or over-exploitation.